2019
DOI: 10.1038/s41467-019-10275-0
|View full text |Cite
|
Sign up to set email alerts
|

SORLA regulates endosomal trafficking and oncogenic fitness of HER2

Abstract: The human epidermal growth factor receptor 2 (HER2) is an oncogene targeted by several kinase inhibitors and therapeutic antibodies. While the endosomal trafficking of many other receptor tyrosine kinases is known to regulate their oncogenic signalling, the prevailing view on HER2 is that this receptor is predominantly retained on the cell surface. Here, we find that sortilin-related receptor 1 (SORLA; SORL1 ) co-precipitates with HER2 in cancer cells and regulates HER2 subcellular distr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(86 citation statements)
references
References 51 publications
13
73
0
Order By: Relevance
“…Internalized virus particles in early endosomes are delivered to late endosomes/lysosomes in which membrane fusion occurs. Co-localization of the HER2/ TYRO3 complex and the EBOVΔVP30 particles was detected only when the virus particles were on the cell surface and was no longer detected after internalization (Fig 7E), which may be because HER2 is quickly recycled to the cell surface or is resistant to internalization [40,41]. A similar observation was reported for AXL co-localization with a pseudotyped virus with EBOV GP on its cell surface; their co-localization was not detected once the virus entered the cells [21].…”
Section: Discussionmentioning
confidence: 99%
“…Internalized virus particles in early endosomes are delivered to late endosomes/lysosomes in which membrane fusion occurs. Co-localization of the HER2/ TYRO3 complex and the EBOVΔVP30 particles was detected only when the virus particles were on the cell surface and was no longer detected after internalization (Fig 7E), which may be because HER2 is quickly recycled to the cell surface or is resistant to internalization [40,41]. A similar observation was reported for AXL co-localization with a pseudotyped virus with EBOV GP on its cell surface; their co-localization was not detected once the virus entered the cells [21].…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies have been conducted in other types of tumors. Mika et al found the SORLA-dependent molecular pathway in HER2-driven cancers [46]. Yoshihisa et al suggested that syn-miR-143 down-regulated the expression of HER2 through silencing DEAD/H-box RNA helicase 6 (DDX6) in HER2-positive gastric cancer cells [47].…”
Section: Discussionmentioning
confidence: 99%
“…These studies underline the versatility of LRP1 functions in breast TME and support ongoing research to identify the specific molecular interfaces mobilized by the receptor that could be targeted to control aggressive behavior of tumor cells. A less characterized member of LRPs, SorLA/LRP11, was recently involved in the endocytic trafficking of HER2 ( 20 ). The depletion of SorLA was reported to affect lysosomal function and sensitize HER2-overexpressing cells resistant to targeted therapy.…”
Section: Lrps and Breast Cancer Cells: A Close And Complex Relationshmentioning
confidence: 99%